EFFECTS OF MSC-DERIVED SECRETOME TOWARDS PLASMA-TOTAL CHOLESTEROL LEVELS ON ROTENONE-INDUCED PARKINSON’S DISEASE RAT MODELS - Putria, Fani Mustika; Sasmita, Poppy Kristina; Sidharta, Veronika Maria; Ardianto, Christian; Barus, Jimmy (MNJ (Malang Neurology Journal), 2025)
Background: Parkinson's disease (PD), a chronic progressive neurodegenerative disease, threatens much of the world's increasingly aging population and has no promise for disease-modifying drugs, only symptomatic treatment. One potential biomarker correlates PD to the disruption of cholesterol metabolizing processes that results in formation of cytotoxic bile acids (BA) which induces mitochondrial dysfunction that leads to the decrease of dopaminergic neurons in various PD models. Objective: This study aims to determine the effect of rotenone-induction as well as MSC-Secretome administration on plasma-total cholesterol levels in rat models.. Methods: This was an experimental research using 30 male Sprague Dawley rats divided into sham control, rotenone (+) secretome (-) and rotenone (+) secretome (+). Blood was withdrawn on day 0 and day 8 and analyzed under colorimetry and spectrophotometry for its plasma-total cholesterol concentration. Results: The Tukey Post-Hoc Test showed that there was no significant difference between the sham control and rotenone (+) secretome (-)  (p = 0.073), plasma-total cholesterol level is lower in rotenone (+) secretome (-) than in the sham control. Furthermore, we were unable to prove for a significant difference between the rotenone (+) secretome (-) and rotenone (+) secretome (+) group (p= 0.234), even though in average the plasma-total cholesterol level is lower in the rotenone (+) secretome (+)  group. Conclusion: Induction of rotenone followed by an intervention of MSC-Secretome has no effect on the change in plasma-total cholesterol levels on rat models.